Cerebral oxygenation reflects fetal development in preterm monochorionic and dichorionic twins - Korček, Peter; Širc, Jan; Straňák, Zbyněk (Early human development, 2020)
BACKGROUND: Cerebral oxygenation (crSO2) monitoring is increasingly used in high-risk infants. Monochorionic twins suffer from specific fetal pathologies that can affect cerebral hemodynamics. Limited data are available on crSO2 and blood flow patterns in this population after birth. OBJECTIVE: To evaluate crSO2 changes in preterm monochorionic and dichorionic twins during the first 72 h of life. METHODS: Near-infrared spectroscopy was used to measure crSO2 in 62 infants from 31 twin pregnancies <32 weeks of gestation. The study group was divided into 4 subgroups: donor (1) and recipient (2) monochorionic twins (with twin-twin transfusion syndrome), fetal growth restriction (FGR) infants (3) and twins without fetal compromise (4). RESULTS: There was significant difference in birth weight (p < 0.001) among 4 subgroups. We observed significant variation in crSO2 among the subgroups using mixed model analysis (p < 0.001). The recipient twins exhibited the lowest crSO2 (mean ± SE) throughout the study period (76 ± 0.3%), whereas the FGR and donor twins presented with the highest values (86 ± 0.3% and 83 ± 0.4% respectively). We found no statistically significant differences in neonatal mortality and morbidity among subgroups. CONCLUSION: Our study revealed significant correlation between crSO2 values postnatally and underlying fetal pathology in monochorionic and dichorionic preterm twins.
Keywords: Fetal Growth Retardation; růstová retardace plodu; Pregnancy, Twin; Prospective Studies; těhotenství; Humans; mozkový krevní oběh; prospektivní studie; Oxygen; Fetal Development; porodní hmotnost; dvojčata dizygotní; Cerebrovascular Circulation; Twins, Dizygotic; chorion; Infant, Newborn; Birth Weight; fetofetální transfuze; Fetofetal Transfusion; novorozenec; kyslík; ženské pohlaví; lidé; Infant, Premature; Pregnancy; Spectroscopy, Near-Infrared; blízká infračervená spektroskopie; těhotenství s dvojčaty; vývoj plodu; Chorion; novorozenec nedonošený; Female